Der Schriftsteller in medialer Kommunikation mit der Öffentlichkeit. Überlegungen aus fremdkulturwissenschaftlicher Sicht aus Anlass des 80. Geburtstags von Martin Walser - Wolting, Stephan (Glottodidactica, 2007)
The present article tries to attract attention to the public appearance of one of the most famous and controversial writers in German language, Martin Walser, who celebrated his 80th birthday in 2007. On the occasion of this anniversary the essay focuses on the question of the impact and the effect of the author, not only by his works, but by his talks and speeches in the mass media too.